Deprivation of Muscleblind-Like Proteins Causes Deficits in Cortical Neuron Distribution and Morphological Changes in Dendritic Spines and Postsynaptic Densities - Lee, Kuang-Yung; Chang, Ho-Ching; Seah, Carol; Lee, Li-Jen (Frontiers in Neuroanatomy, 2019)
Myotonic dystrophy (Dystrophia Myotonica; DM) is the most common adult onset muscular dystrophy and brain symptoms seriously affect patient’s quality of life. The Muscleblind-like (MBNL) proteins are splicing factors regulating posttranscriptional RNA during development. Previously, Mbnl KO mouse lines showed molecular and phenotypic evidences that recapitulating DM brains, however, detail morphological study has not yet been accomplished. In our studies, control (Mbnl1+/+; Mbnl2cond/cond; Nestin-Cre-/-), Mbnl2 conditional knockout (2KO, Mbnl1+/+; Mbnl2cond/cond; Nestin-Cre+/-) and Mbnl1/2 DKO (DKO, Mbnl1ΔE3/ΔE3; Mbnl2cond/cond; Nestin-Cre+/-) mice were generated by crossing three individual lines. Immunohistochemistry for evaluating densities and distributions of cortical neurons; Golgi staining for depicting the dendrites/dendritic spines; and electron microscopy for analyzing postsynaptic ultrastructure were performed. We found migratory defects in cortical neurons, reduction in dendritic complexity, immature dendritic spines and alterations of postsynaptic densities in the mutants. In conclusion, loss of function of Mbnl1/2 caused fundamental defects affecting neuronal positioning during migration, dendritic morphology and postsynaptic architectures that are reminiscent of predominantly immature and fetal phenotypes in DM patients.